Electromagnetic Wave Scattering by Aerial and Ground Radar Objects - Sukharevsky, Oleg I. (Taylor & Francis, 2015)
Electromagnetic Wave Scattering by Aerial and Ground Radar Objects presents the theory, original calculation methods, and computational results of the scattering characteristics of different aerial and ground radar objects. This must-have book provides essential background for computing electromagnetic wave scattering in the presence of different kinds of irregularities, as well as Summarizes fundamental electromagnetic statements such as the Lorentz reciprocity theorem and the image principle Contains integral field representations enabling the study of scattering from various layered structures Describes scattering computation techniques for objects with surface fractures and radar-absorbent coatings Covers elimination of "terminator discontinuities" appearing in the method of physical optics in general bistatic cases Includes radar cross-section (RCS) statistics and high-range resolution profiles of assorted aircrafts, cruise missiles, and tanks Complete with radar backscattering diagrams, echo signal amplitude probability distributions, and other valuable reference material, Electromagnetic Wave Scattering by Aerial and Ground Radar Objects is ideal for scientists, engineers, and researchers of electromagnetic wave scattering, computational electrodynamics, and radar detection and recognition algorithms.